Apprenticeship in the Renaissance University: Student authorship and craft knowledge. Issue 2 (June 2019) - Oosterhoff, Richard J.
Argument: Students entered Renaissance universities as apprentices in the craft of books. In the decades around 1500, such university training began to involve not only manuscript circulation, but also the production and the use of books in the new medium of print. Through their role in the crafting of books, I show how a circle of students around Jacques Lefèvre d'Étaples gained the experience needed to become bookmen. Students took classroom manuscripts and brought them into print – the new print shop offered students a place in which to exchange labor for credibility as joint authors.